PENGARUH HARGA, PROMOSI, KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN JASA OJEK ONLINE â€œOM-JEKâ€ JEMBER - Anggriana, Rina; Qomariah, Nurul; Santoso, Budi (Universitas Muhammadiyah Jember, 2017)
ABSTRACTBusiness services today are increasingly diverse in order to meet the needs of people's lives. Business services is one business that strives to create customer satisfaction. One of the services business that is developing at this time is the business of two-wheeled transpotation services or often referred to by the name of motorcycle taxi. The purpose of this study is to determine and analyze the influence of price, promotion, quality of service to customer satisfaction partially. The population in this study is the customer